INFLUENCE OF TEAM-TEACHING ON THE PERFORMANCE OF MATHEMATICS IN PUBLIC SECONDARY SCHOOLS IN MAKUENI SUB-COUNTY, KENYA - Muli, Mutuku Andrew; Wamitu, Susan Njeri (European Journal of Business and Strategic Management, 2019)
Purpose: Strategic management is a concept that is concerned with making decisions and taking corrective actions to achieve long term targets, objectives and goals of an organization. The main purpose of this study was to determine the influence of team-teaching on the students' performance in Mathematics in public secondary schools in Makueni Sub-County. Methodology: This study adopted a descriptive survey research design and the study targeted the 46 registered public secondary schools in Makueni Sub-County. Two sampling techniques were used; census on the school principals and systematic random sampling of 30% of the Mathematics teachers from every school to obtain a sample size of 118 study participants. Data collection was carried out through administration of questionnaires. Data was analyzed using descriptive and inferential statistics with the help of statistical package for social scientists (SPSS) version 21, discussed and presented in tables. Findings: Descriptive statistics and regression analysis indicated that there was a positive relationship between team-teaching and performance in Mathematics. The findings of this study were in agreement with those of the previous studies reviewed. The study concluded that team-teaching is a major predictor of the students' performance in Mathematics. Unique Contribution to Theory, Practice and Policy:The study recommended that the school administrators and other stakeholders in secondary schools in Makueni Sub-County should embrace team work as teachers for students' optimum performance in their respective secondary schools.